Commentary on Venner et al. : Community‐based participatory research opens doors to rigorous addiction treatment research with Indigenous communities - Skewes, Monica C. (Addiction (Abingdon, England), 2021)
Despite significant health disparities and great need for treatment, few evidence‐based treatments for substance use disorder have been tailored to or tested with American Indian/Alaska Native communities. Community involvement through community‐based participatory research is necessary for advancing scientific knowledge and addressing treatment disparities.